The impact of bequest motives on retirement behavior in Japan: A theoretical and empirical analysis - Charles Horioka; Emin Gahramanov; Aziz Hayat; Xueli Tang (Osaka University, Institute of Social and Economic Research (ISER), 2020)
In this paper, we conduct a theoretical and empirical analysis of the impact of bequest motives on the work and retirement behavior of households in Japan using micro data from the Preference Parameters Study of Osaka University. Our empirical findings are consistent with our theoretical model and show that respondents with an altruistic or strategic/exchange bequest motive work more at the intensive margin than those without any bequest motive but that respondents with a strategic or exchange bequest motive work less at the extensive margin (i.e., retire earlier) than those without any bequest motive. Our findings for the strategic or exchange motive suggest that respondents with such a motive tend to work harder than others before they retire so that they can earn more, leave a larger bequest to their children, and elicit more care from them but that they tend to retire earlier than others so that they can start receiving care for themselves and their spouses from their children sooner. A policy implication of our findings is that the exchange of bequests for the care of parents by children may be very sensitive to the inheritance tax framework.
Keywords: D15; D64; J14; J22; J26; 330; Altruistic bequest motive; bequest motives; exchange bequest motive; inheritances; Japan; labor supply; retirement; strategic bequest motive; working hours